REFLECTION OF THE FIGURATIVE EXPRESSIONS OF THE LANGUAGE IN TRANSLATIONS (Scientific journal of the Fergana State University, 2023)
We all know that the use of figurative expressions available in the language gives effective results in expressing the ideas expressed in the language in an understandable, effective, and, moreover, figurative way. This article deals with the issue of the use of figurative expressions in socio-political works and their translation.